Numerical Simulation of Water Mitigation Effects on Shock Wave with SPH Method - 毛益明 方秦 张亚栋 高振儒 (Transactions of Tianjin University, 2008)
The water mitigation effect on the propagation of shock wave was investigated numerically. The traditional smoothed particle hydrodynamics （SPH） method was modified based on Riemann solution. The comparison of numerical results with the analytical solution indicated that the modified SPH method has more advantages than the traditional SPH method. Using the modified SPH algorithm, a series of one-dimensional planar wave propagation problems were investigated, focusing on the influence of the air-gap between the high-pressure air and water and the thickness of water, The numerical results showed that water mitigation effect is significant. Up to 60% shock wave pressure reduction could be achieved with the existence of water, and the shape of shock wave was also changed greatly. It is seemly that the small air-gap between the high-pressure air and water has more influence on water mitigation effect.